ประสบการณ์การเป็นพยาบาลผ่าตัดที่ปฏิบัติงานในโรงพยาบาลตติยภูมิของรัฐ - พราวนภา ภู่รัตนากรกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purpose of this research was to describe lived experiences of being a perioperative nurse working in a tertiary government hospital. Hermeneutic phenomenology of Martin Heidegger was applied as research methodology. Data were collected by using in-depth interviews of 14 perioperative nurses working at a tertiary government hospital and having more than 3 years of working experience. Data was analyzed by using Crist and Tanner s method of content analysis. The results of the research revealed 5 themes as follows: 1. Reasons for working as a perioperative nurse, including 2 sub-themes: (1.1) providing care for a short period of time. (1.2) being challenge and involving decision making with surgeon. 2. Seeking knowledge and experiences when being a new perioperative nurse, including 4 sub-themes : (2.1) being exciting and stressful, (2.2) asking for the answers and keep practicing, (2.3) updating knowledge, and (2.4) gaining experience from mistakes 3. Several experiences when working as circulated and scrub nurses, including 2 sub-themes : (3.1) checking work schedule and preparing for work, and (3.2) working as a team. 4. Focusing on patients when working in an operative room, including 3 sub-themes: (4.1) providing safety and comfortable, (4.2) saving patient’s life is our concern, and (4.3) being careful when operation, one mistake can lead to complication 5. Working for a long period of time may cause health problems, including 4 sub-themes: (5.1) eating late and no time to go to the toilet, (5.2) having muscular pain, (5.3) being risk from air pollution, and (5.4) being exhaust if working all day and night. The study findings of the meanings and experiences could lead to the better management system in an operation room and lead to improve efficiency of perioperative nurses in a tertiary government hospital.